Uji Antifungi Ramuan Tradisonal Madura â€œSubur Kandunganâ€ - Savitri, Evika Sandi (Al-Kauniyah: Jurnal Biologi, 2015)
Jamu herb Madura "Kandungan Subur" for women's reproductive health widely consumed to overcome the problem of reproduction. Some species are used traditional ingredients "Lush content" is Curcuma longa, Curcuma zedoria, Centella asiatica, Foeniculi dulcis; there has been no scientific studies and standardization adequate to ensure the safety and usefulness. To answer these problems, need to be screened early stage potential medicinal plants used in herbal Madura is an analysis of potential medicinal plants such as antifungal and phytochemical content contained. The extraction of active compounds with maceration, test active phytochemical compounds with the test reagents. Antifungal test includes a minimum inhibitory concentration and minimum killing concentration. Compounds contained in the herb "Fertile Content" are flavonoids and alkaloids.Â  Ethanol extract of 70% and 100% can inhibit the growth of fungi at a concentration of 1%.